Peran dan Motivasi Pendidikan dalam Pendidikan Islam melalui Pendekatan Pengalaman, Pendekatan Pembiasaan, Pendekatan Emosional - Restu Dini; Aminuddin Aminuddin (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2022)
Education can be interpreted as conscious guidance by educators on the physical and spiritual development of students towards the formation of the main personality. So that education is seen as one aspect that has a major role in shaping the younger generation to have a major personality. With the education scheme, educators can achieve the targets and patterns of educational development in various ways, including the good approach, the experiential approach, the habituation approach, and the emotional approach. Islamic religious education is an effort in the form of guidance and care for students so that later after completing their education they can understand and practice the teachings of Islam and make it a way of life.